2016
DOI: 10.1002/hbm.23359
|View full text |Cite
|
Sign up to set email alerts
|

Precuneus degeneration in nondemented elderly individuals with APOE ɛ4: Evidence from structural and functional MRI analyses

Abstract: Neurodegenerative diseases such as Alzheimer's disease (AD) have been recognized to exhibit disease-specific brain vulnerability patterns. Apolipoprotein E (APOE) ɛ4 allele imparts a high genetic risk of developing AD. Whether the APOE ɛ4 allele damages the brain when cognitive functions are still intact is important to understand, especially for possible early detection and intervention. This study aimed to examine the selective degeneration pattern associated with the APOE ɛ4 allele in the brains of cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 65 publications
3
20
0
1
Order By: Relevance
“…This finding may be partly consistent with other previous studies, which suggested that the hippocampus may be affected as depression progresses rather than in the subclinical stage of depression (Hayakawa et al, 2013;Taki et al, 2005). In addition, previous studies have reported that asymptomatic APOE ε4 carriers in healthy elderly showed structural changes in the precuneus exclusively, and not in the hippocampus (Brown et al, 2011;Chen et al, 2017). The current study may support that the alteration in connectivity strength of the hippocampus is progressionspecific in the case of SMCs and depression.…”
Section: Discussionsupporting
confidence: 83%
“…This finding may be partly consistent with other previous studies, which suggested that the hippocampus may be affected as depression progresses rather than in the subclinical stage of depression (Hayakawa et al, 2013;Taki et al, 2005). In addition, previous studies have reported that asymptomatic APOE ε4 carriers in healthy elderly showed structural changes in the precuneus exclusively, and not in the hippocampus (Brown et al, 2011;Chen et al, 2017). The current study may support that the alteration in connectivity strength of the hippocampus is progressionspecific in the case of SMCs and depression.…”
Section: Discussionsupporting
confidence: 83%
“… Erk, et al 2011 [48] 19 subjective memory impairment, 20 CNC Face-profession association ROI (HC, DLPFC) Reduced right HC activation, increased right DLPFC activation in subjective memory impairment group. Chen, et al 2017 [49] 35 APOE ε4 carrier, 40 noncarrier CNC Picture encoding Seed ROI based on group cortical morphology differences and DMN/cortical thickness Reduced precuneus deactivation, reduced postcentral, precentral, inferior occipital gyri, inferior parietal lobule activation in APOE ε4 carriers. MCI Johnson, et al 2006 [50] 14 MCI, 14 CNC Picture encoding Reference group activation Reduced R HC head and body, L lateral frontal, R inferior temporal lobe activation in MCI during novel pictures.…”
Section: Functional Mrimentioning
confidence: 99%
“…e precuneus also assists other brain regions in performing functions such as information processing, especially in regards to emotion regulation [59,60]. Furthermore, the precuneus is a major hub of brain organization and a central node of DMN [61,62].…”
Section: Discussionmentioning
confidence: 99%